Pengembangan Modul Pembelajaran Mikrokontroler Berbasis Online untuk Mahasiswa Teknik Elektro - Irsyad Syawal; Ta'ali Ta'ali (Jurnal Pendidikan Teknik Elektro, 2021)
This research discusses the development of online-based learning modules in microcontroller courses. self-instructional learning modules that direct students to learn independently. Due to conditions and situations that do not allow for face-to-face learning due to the covid-19 pandemic that forces learning to be done online. Therefore, online-based modules are one of the effective means used to delve into the material and evaluate themselves independently, so as to optimize learning outcomes. The purpose of this research is to develop valid and practical learning modules. Based on the results of the study obtained the validity of learning modules from two validators consisting of two expert lecturers obtained an average achievement rate of 79.3% with valid categories. The practicality test with respondents consisting of one electrical engineering lecturer obtained an achievement level of 80% with practical categories and respondents consisting of 15 students of D3 Electrical Engineering obtained an average achievement rate of 78.2% with practical categories. From the research data described, it can be concluded that online-based learning modules in Microcontroller courses are valid and practical.